POTENTIAL NATURAL TOURISM AREA IN SUPPORTING THE ASAHAN GO WISATA PROGRAM (Case of Asahan River Rafting Tour, Asahan Regency) - Rahmad Kurnia Abdik Nasution; Emrizal Emrizal; Marciella Elyanta (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
The objectives of this study are: To analyze the ecotourism potential in the Asahan River Rapids area based on the ECOS (Ecotourism Opportunity Spectrum). This qualitative descriptive study uses four data collection techniques: observation, interviews, questionnaires, and documentation. The sampling technique in this study uses non-probability precisely, namely Purposive Sampling and Incidental Sampling. Then the data obtained were analyzed using the ECOS approach. Research shows that the potential for ecotourism in the Asahan River Rapids area based on the ECOS approach is to have an Eco Specialist indicator. Where these indicators are assessed using seven components in ECOS, namely the access component with the Eco Specialist indicator, other related resource components with the intermediate indicator, the attraction component with the Eco Specialist indicator, the infrastructure component with the Eco Specialist indicator, and the social interaction component with the Eco indicator. Specialist, component level of ability and knowledge with indicator Intermediate, and the component of visitor impact with indicator Intermediate.